An anatomy of the crude oil pricing system - Bassam Fattouh (The Oxford Institute for Energy Studies, 2011)
The main purpose of this report is to analyse the main features of the current crude oil pricing system; to describe the structure of the main benchmarks currently used namely Brent West Texas Intermediate (WTI) and Dubai-Oman; to clearly identify the various financial layers that have emerged around these physical benchmarks; to analyse the links between the different financial layers and between the financial layers and the physical benchmarks; and then to evaluate how these links influence the price discovery and oil price formation process in the crude oil market. The report finds that the assumption that the process of identifying the price of benchmarks in the current oil pricing system can be isolated from financial layers is rather simplistic. The different layers of the oil market are highly interconnected and form a complex web of links, all of which play a role in the price discovery process. The report also calls for broadening the empirical research to include the trading strategies of physical players; any analysis limited to non-commercial participants in the futures market and their role in the oil price formation process is incomplete. The report also emphasises the distinction between trade in price differentials and trade in price levels and finds that the level of the oil price, which consumers producers and their governments are most concerned with is not the most relevant feature in the current pricing system. Instead the identification of price differentials and the adjustments in these differentials in the various layers underlie the basis of the current oil pricing system.
Keywords: 330; Ölpreis; International; Ölmarkt; Welt